UPAYA PENINGKATAN PEMAHAMAN PESERTA DIDIK DALAM MELAKUKAN PERKALIAN PECAHAN BIASA MELALUI ALAT PERAGA KARTON BERPETAK DAN METODE PEMBERIAN SOAL PADA KELAS V DI SEKOLAH DASAR NEGERI 1 SUKARAME - Ningtyas, S. Tanjung (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to increase the learning achievement in Mathematics subject using PERAGA KARTON BERPETAK tools and questioning method. This study is classroom action research. The participants come from the fifth grade students of SD Negeri 1 Sukarame Bandar Lampung. Based on the result of improved learning is done through classroom action research can be concluded that the application of cardboard props and media terraced Student Worksheet to find ways multiplying fractions in learning mathematics in Class V SD Negeri 1 Sukarame has been able to increase the field of Mathematics Learners.